Infragluteal fasciocutaneous flap for management of recurrent ischial pressure sore - Kumar, Umesh; Jain, Pradeep (Indian Journal of Plastic Surgery, 2018)
Objective: The objective of the study was to determine the feasibility of infragluteal fasciocutaneous flap in recurrent ischial pressure sore. Materials and Methods: In our study, from 2015 to 2017, nine patients suffering from recurrent ischial sore with scars of previous surgery were managed with infragluteal fasciocutaneous flap. Wound bed was prepared by surgical debridement and negative pressure wound therapy in each case. In two cases, gracilis muscle flap was used as adjuvant to fill up the residual cavity. Donor area of flap was primarily closed. Results: Infragluteal fasciocutaneous flap was used in all nine cases. Superficial distal congestion was present in two cases. Haematoma (1) and infection (1) at flap donor site occurred. Recurrence of ulcer was observed in two cases which were managed by bursectomy and advancement of the bridge segment of the original infragluteal fasciocutaneous flap. All flaps survived without any major complication. Discussion: Ischial pressure sores have a tendency of recurrence after conservative or flap surgery. Scars due to previous surgeries adjacent to the pressure sore preclude the use of local skin or muscle flap. Infragluteal fasciocutaneous flap is a thick reliable fasciocutaneous flap that can be used for resurfacing recurrent ischial pressure sore. This flap has an axial pattern blood supply along with rich subfascial and fascial plexus supplied by various perforators. Conclusion: Infragluteal fasciocutaneous flap is reliable option for managing recurrent ischial sore as it transposes well-vascularised thick fasciocutaneous flap from adjacent posterior thigh and its bridge segment can be further used in case of recurrence.
Keywords: Infragluteal fasciocutaneous flap; ischial pressure sore; perforator plus flap; recurrent pressure ulcer